Substantiation of method for calculating design parameters of horizontal hydraulic classifier - Franchuk, V.P.; Bondarenko, A.A.; Titov, A.A. (Геотехнічна механіка, 2017)
Process of gravitational treatment of granular materials in the pulp horizontal flow is accompanied by bearing stream flowing within differently inclined surfaces and by downstream of condensed pulp. In the article, method for calculating design parameters of horizontal classifier is validated, which is based on construction of trajectories of solid particle motion. Процесс гравитационной переработки зернистых материалов в горизонтальном потоке пульпы сопровождается течением несущего потока в пределах разнонаклонных поверхностей, а также оттоком вниз сгущенной пульпы. В работе обоснован метод расчета конструктивных параметров горизонтального классификатора, который основан на построении траектории движения твердых частиц. Процес гравітаційної переробки зернистих матеріалів у горизонтальному потоці пульпи супроводжується рухом несучого потоку в межах різнопохилих поверхонь, а також відтоком донизу згущеної пульпи. У роботі обґрунтований метод розрахунку конструктивних параметрів горизонтального класифікатора, заснований на побудові траєкторії руху твердих частинок.